Real-time Key Management for Wireless Mesh Network - Hoa, Le Viet; Vinh, Truong Quang (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
With the rapid technological development of wireless, wireless mesh network (WMN) is one of the network models which is gradually showing its superiority through several applications and projects thus it is becoming the key of technology for IoT. Due to the vulnerable environment, limited resource and open communication channel, the security design for such networks are significantly challenging. By using realtime synchronization method between transceiver devices in the WMNs, we propose an algorithm based on secret sharing method in which each node generate its key depend on its physical information and the real-time clock. Therefore, we can manage efficiently public and private keys for data encryption and prevent several external attacks to WMNs. We also propose a specific protocol to secure our keys while transferring between devices to prevent internal attacks.